Plenty of Room at the Top: A Multi‐Scale Understanding of nm‐Resolution Polymer Patterning on 2D Materials. (25th October 2021) - Shi, Anni; Villarreal, Terry A.; Singh, Anamika; Hayes, Tyler R.; Davis, Tyson C.; Brooks, Jacob T.; Claridge, Shelley A.
Abstract: Lamellar phases of alkyldiacetylenes in which the alkyl chains lie parallel to the substrate represent a straightforward means for scalable 1‐nm‐resolution interfacial patterning. This capability has the potential for substantial impacts in nanoscale electronics, energy conversion, and biomaterials design. Polymerization is required to set the 1‐nm functional patterns embedded in the monolayer, making it important to understand structure–function relationships for these on‐surface reactions. Polymerization can be observed for certain monomers at the single‐polymer scale using scanning probe microscopy. However, substantial restrictions on the systems that can be effectively characterized have limited utility. Here, using a new multi‐scale approach, we identify a large, previously unreported difference in polymerization efficiency between the two most widely used commercial diynoic acids. We further identify a core design principle for maximizing polymerization efficiency in these on‐surface reactions, generating a new monomer that also exhibits enhanced polymerization efficiency. Abstract : Striped phase polydiacetylenes create 1‐nm‐resolution chemical patterns on 2D materials, well below the limits possible through most fabrication methods. A new multi‐scale view of polymerization enables the design of monomers that undergo efficient on‐surface polymerization, opening the door to new applications that rely on stable, near‐atomic‐scale chemical environments.